The Development Early Warning System to Prevent Bullying in University, Jakarta, Indonesia - Hendrayani, Yani; Sutowo, Irfan; T, Danish; Saputra, . (KnE Social Sciences, 2022)
Bullying is a commonly reported phenomenon in Indonesian schools and universities – prepetrated by seniors and, in some cases, classmates. This study was conducted at a state defense campus to examine the types of bullying faced by students and the ways to stop/prevent them. The authors used a mixed-method combining quantitative and qualitative research methodologies. Data were collected by distributing questionnaires to all students (a total population of 11,365) and selecting a sample of 1% (114 students). The authors interviewed leaders of the Student Affairs sector and conducted Focus Group Discussions with 10 representatives of student organizations from each faculty. The results indicated cases of relational bullying – a condition in which self-esteem is weakened by neglect, exclusion, and avoidance. The authors found that the bullying tendencies stemmed from the bullies’ own personal and social experiences. Additionally, schools must train their Academic Advisors to ensure that protection from bullying in no way affects students’ learning motivation. The authors expect this system to develop into an Early Warning System (SPD) for improving student excellence and to be implemented at all campuses considering the interrelated environmental, social, cultural, vision, and mission aspects of it. Keywords: bullying, academic advisors, early warning system